2011
DOI: 10.3390/ma4030562
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Photophysical Properties of Pyridine-Carbazole Acrylonitrile Derivatives

Abstract: Abstract:We synthesized three novel highly fluorescent compounds, 2-(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Therefore, higher values of E HOMO indicate a better tendency towards the donation of electron and energy of the lowest unoccupied molecular orbital (E LUMO ) indicates the ability of the molecule to accept electrons. Comparing the FMO energy values of the acrylonitrile derivatives, I – V containing 2,4,5-TMeO- with reported compounds [ 46 , 47 , 48 , 49 , 50 , 67 ] substituted with F, Cl, Br, -N(CH3) 2 , -N(Ph) 2 , -Cz, chalcones, and ring phenyl ring or pyridine ring in ortho , meta and para positions, we found that E LUMO values indicated I – V are better electron acceptors than electron donors ( Figure 5 and Figure S14 ) and are able to interact with solvents because the HOMO and LUMO values are very close. The experimental and calculated absorption wavelengths in all solvents are summarized in Table S6 and the calculated absorptions in Figures S11–S13 , as well as the HOMO and LUMO of the solvents, Figure S15 , and Table S7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, higher values of E HOMO indicate a better tendency towards the donation of electron and energy of the lowest unoccupied molecular orbital (E LUMO ) indicates the ability of the molecule to accept electrons. Comparing the FMO energy values of the acrylonitrile derivatives, I – V containing 2,4,5-TMeO- with reported compounds [ 46 , 47 , 48 , 49 , 50 , 67 ] substituted with F, Cl, Br, -N(CH3) 2 , -N(Ph) 2 , -Cz, chalcones, and ring phenyl ring or pyridine ring in ortho , meta and para positions, we found that E LUMO values indicated I – V are better electron acceptors than electron donors ( Figure 5 and Figure S14 ) and are able to interact with solvents because the HOMO and LUMO values are very close. The experimental and calculated absorption wavelengths in all solvents are summarized in Table S6 and the calculated absorptions in Figures S11–S13 , as well as the HOMO and LUMO of the solvents, Figure S15 , and Table S7 .…”
Section: Resultsmentioning
confidence: 99%
“…The optical properties can also be altered by substituents located in various positions around the molecular structure [ 41 , 43 , 44 ]. Especially, the optical properties of compounds containing a pyridine ring and with α-cyanostilbenes with dimethylamine, diphenylamine, halogen atoms and N -ethylcarbazole substituents have been reported [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. It has been established that molecules are not emitters in solution (SCQ) [ 54 , 55 ], which prompted us to question why are such compounds not emitters?…”
Section: Introductionmentioning
confidence: 99%
“…The observed data also corroborates an assumption about the essential role of the cyano group in the pyridine ring causing the high uorescence of the pyridine derivatives and allows it to act as an excellent uorescent core with good electron-transporting properties. [46][47][48][49][50][51][52] It can be easily observed from the study that our nicotinonitrile-based uorescent type molecules containing pyrene and/or uorene moieties have been proven to be promising uorophores for application as chemo-and biosensors. Moreover, this type of structure with a highly electron decient system could be of interest to many researchers working on the development of n-type organic semiconductors and for the design of new liquid crystal materials.…”
Section: Substituent Effect On Absorption and Emission Spectra Of Thementioning
confidence: 99%
“…Additionally, they have been used as photorefractive polymers, holographic recording materials, and fluorescent probes for different metal ions sensing [14][15][16][17][18][19][20]. On the other hand, the polycyclic aromatic hydrocarbons such as naphthalene, phenanthrene, and pyrene have strong absorption cross section, excellent emission properties, and long excited state lifetime compared to simple phenyl analogue [21,22].…”
Section: Introductionmentioning
confidence: 99%